(untitled) - Lee, Chin-Hwa (California, 1992)
Helps us using VHDL in design digital system
Keywords: Electronic digital computers,System design,Máy tính kỹ thuật số điện tử,Thiết kế hệ thống; Circuits,Data processing,Mạch,Thiết kế máy tính hỗ trợ,Xử lý dữ liệu; Computer-aided design